ANALYSIS OF ORGANIC AND ANORGANIC DEBRIS IN AIR MANIS BEACH, NIRWANA BEACH AND CAROLINA BEACH OF PADANG CITY WEST SUMATERA PROVINCE - Aditya, M; Amin, Bintal; Elizal, Elizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2019)
This research was conducted in June 2019 to determine the kind of marine debris, source, production and the correlation with the number of tourists in Air Manis, Nirwana, and Carolina Beach of Padang City, West Sumatera. Three sampling stations were surveyed. The results showed that marine debris found in those beaches were categoryses organic, such as: fruits, leaves, wood, bamboo, sea plants and else anorganic especially: plastic, glass, rubber, metal, etc. Air Manis Beach had the highest production of marine debris (1340 pcs), followed by Nirwana Beach (538 pcs) and Carolina Beach (500pcs). The source of marine debris were assessed to come from visitors and from outside those beac hes carried by sea current. The total of marine debris production was 29.165 kg. Plastic was the most common type of debris found. The production of garbage in the number of visitors shows very strong relationships (Y = -94,505 + 2,018x ; r = 0,97 ). There is strong correlation between the number of visitors and marine debris production in those beaches